Educação inclusiva no ensino superior: o docente universitário em foco - Santos, Amanda Fernandes (2009)
This research is concerned with the attention given by professors to issues that include inclusive education in higher education. Has as main objective to identify the concepts of disability, of the training of teachers and the teaching-learning process that university students have forward the issue of inclusive education, to understand whether these concepts fit or not to practice inclusive. Was used the quanti-qualitative methodology through the application of a questionnaire with three items, conceptions of disability, teacher training and teaching-learning process, whereby for each of these, five issues were willing, analyzed statistically using the analysis tool SPSS 16.0. In this sense, the research local was a university in the Southeast region of Brazil, and the participants were 27 professors under the exclusive dedication of the Pedagogy Course, Faculty of Education of the same university. The research has concluded that the participating professors are concerned with issues of special education, since to the majority (66.7%) is very important the physical and academic adjustments to the university students with disabilities can complete the training in a satisfactory manner. However, few (26%) have continued training in the area, demonstrating the need for the disclose experiences and researches completed on the subject. Thus, the three items cover the main theoretical issues worked, outlining the characteristics of participating teachers about their concerns in the practice of inclusive education. The study proves the existence of the need for continued work to ensure that special education be present in Brazilian universities, having centers that help professors and students with disabilities to adapt to model of inclusive education. Considers the importance of the organization of the continuing education for the entire university population, because the information about special education allows the universities are appropriate for inclusive education.